Export Diversification through Bonded Warehouse Reforms - World Bank (World Bank, Washington, DC, 2018)
Benefits and rules of bonded manufacturing are often discretionary. Bonded manufacturing is a form of temporary admission, which is equivalent to suspended import duty. The term used varies from country to country: Special Bonded Warehouses (SBW) in Bangladesh, Export Only Units in India, Bonded Manufacturing Warehouses in Malaysia, etc. The rules under which they operate also vary substantially from country to country and have changed over time. Bonded manufacturing status allows firms to bring imported goods into their warehouses without paying import duty, use the goods in their production, and export the output. The firms can usually also import machinery and replacement parts and other supplies duty-free, and buy from domestic suppliers free of domestic excise, sales and other taxes. The participating factories operate under the supervision of Customs authorities, who check the import and export containers going to and from the bonded factory, or, in some cases, rely on spot checks of the factory's inventories. The benefits and rules are at the discretion of the governments. The success of the bonded warehouse facility is not equitable and inclusive in Bangladesh. Bangladesh’s customs bonded warehouse regime permits licensed manufacturers to import duty-free parts and materials required for their export production purposes. The regime is most heavily used by RMG producers and to a lesser extent by leather goods, footwear, and shipbuilding industries. Enterprises can use the Special Bonded Warehouse (SBW) facility for importing all inputs duty-free along with imports of inputs under back-to-back LC (letters of credit), a facility to pay for imported inputs from export proceeds. This policy works to negate both the effect of relatively high import tariffs and the difficulty in claiming duty drawback on the export of duty-paid imported raw materials. It ensures competitive pricing by exporters for their manufactured goods as they compete in regional (and global) markets. However, these schemes allowing the duty-free import of inputs are not available equally to other sector exporters, who must pay duties on imported inputs upfront and rely on a dysfunctional duty drawback system that involves transaction costs. Therefore, for non-RMG sectors, a tariff on imports becomes a tax on exports on two counts: (a) the higher cost of imported inputs and (b) the higher tariff-induced profitability of Import Substitute Industries that divert resources away from exports.